2022
DOI: 10.3389/fphar.2022.1043527
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota mediated hypoglycemic effect of Astragalus membranaceus polysaccharides in db/db mice

Abstract: Gut microbiota has been reported to be closely associated with Type-II diabetes. Restoration of disordered gut microbiota ecosystem has been developed into a therapeutic strategy and gradually applied on Type-II diabetes treatment with both western drugs and herbal polysaccharides. Although Astragalus membranaceus polysaccharides (AMP) have also been used to treat Type-II diabetes, no study investigated correlations between gut microbiota regulation and its hypoglycemic effect. In the present study, the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…17 Interestingly, the levels of Akkermansia and Faecalibaculum in the gut microbiota have been found to positively correlate with the hypoglycemic effects of Astragalus membranaceus polysaccharides and the alleviation of food allergy symptoms in mice. 30,31 Our findings support the crucial role of Akkermansia and Faecalibaculum in gut microbiota-mediated host health responses and suggest that radiation exposure may impact these important microbial populations. Comparatively, in humans, after allogeneic BMT, there is a decline in bacterial alpha diversity within the first 3 weeks in the gut, oral, and nasal microbiota.…”
Section: Discussionsupporting
confidence: 71%
“…17 Interestingly, the levels of Akkermansia and Faecalibaculum in the gut microbiota have been found to positively correlate with the hypoglycemic effects of Astragalus membranaceus polysaccharides and the alleviation of food allergy symptoms in mice. 30,31 Our findings support the crucial role of Akkermansia and Faecalibaculum in gut microbiota-mediated host health responses and suggest that radiation exposure may impact these important microbial populations. Comparatively, in humans, after allogeneic BMT, there is a decline in bacterial alpha diversity within the first 3 weeks in the gut, oral, and nasal microbiota.…”
Section: Discussionsupporting
confidence: 71%
“…The gut microbiota plays a key role in a variety of diseases. It is suggested that Huangqi repaired the damaged intestinal barrier by regulating the intestinal microbiota, [42] improving cognitive impairment [43] and hypoglycemia, [44] and lowering uric acid. [45] The role of epithelial-mesenchymal transition was a major factor in the development of the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…[37,38] Moreover, high relative abundance of Akkermansia and Faecalibaculum (as observed in Inulin-L and Anti-Inulin-L groups after inulin supplementation stopped), was associated with hypoglycemic effect. [39] Collectively, the dominance of Dubosiella, Akkermansia, and the outgrown Faecalibaculum after restoration, pointed to the longlasting health promoting effect of the supplemented inulin.…”
Section: Discussionmentioning
confidence: 99%